KOBZARS AND LYRNIKS ARE CARRIERS OF CULTURAL MARKERS OF THE ETHNIC IDENTITY OF UKRAINIANS - Сивачук, Н. (Modern engineering and innovative technologies, 2023)
Lyrniks and kobzars in Ukraine have always enjoyed great respect, were carriers of ancient knowledge, moral imperatives, keepers of customs and traditions, carriers of folk pedagogy, ethics, secret knowledge, magic of creativity, language programming, psy